Legal Regulation of State Guarantees Concerning the Rights of Medicine Free Provision for Children in the Russian Federation - M. Khamitova, Gulnara (International Journal of Psychosocial Rehabilitation, 2024)
The problem of securing and protecting citizen rights in the field of medical care within the current legislation is one of the most relevant in modern Russian law. “Health is a state of complete physical, mental, and social well-being, and not just the absence of diseases and physical defects” [1]. A citizen in the Russian Federation, possessing rights and freedoms in the field of medical care, including property and personal nonproperty ones, often faces their declarative nature and neglect in medical practice. The problem of the system's effectiveness increase for ensuring and protecting the rights of patients in Russia requires a qualitative solution. In domestic legislation, the right to protection of health and medical care is enshrined, primarily, in the Constitution of the Russian Federation. Thus, Article 41 enshrines the right to both free medical care in accordance with the program of state guarantees of free medical care for citizens and to receive paid medical services and other services. This article is devoted to compliance with the legislation of the Russian Federation concerning pediatric services. In particular, it considers the procedure for preferential provision of medicines for children under three years of age, as well as for children from large families under six years of age. As the solution to the problem, we propose amending the legislation, and to ensure the implementation of state guarantees, provide prosecutorial supervision in the regions.